2013
DOI: 10.1073/pnas.1305530110
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-oxidizing photosynthesis before the rise of cyanobacteria

Abstract: The emergence of oxygen-producing (oxygenic) photosynthesis fundamentally transformed our planet; however, the processes that led to the evolution of biological water splitting have remained largely unknown. To illuminate this history, we examined the behavior of the ancient Mn cycle using newly obtained scientific drill cores through an early Paleoproterozoic succession (2.415 Ga) preserved in South Africa. These strata contain substantial Mn enrichments (up to ∼17 wt %) well before those associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
149
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 59 publications
9
149
0
Order By: Relevance
“…and that may have been precursors to biological water oxidation catalysts (14). The evidence we provide for δ-MnO 2 photoreduction in the absence of organic electron donors establishes this pathway as an important component of the Mn cycle.…”
Section: Environmental Implicationsmentioning
confidence: 53%
See 2 more Smart Citations
“…and that may have been precursors to biological water oxidation catalysts (14). The evidence we provide for δ-MnO 2 photoreduction in the absence of organic electron donors establishes this pathway as an important component of the Mn cycle.…”
Section: Environmental Implicationsmentioning
confidence: 53%
“…Experimental studies on the photochemical cycling of Mn have incorporated natural organic ligands that can enhance metal reduction via multiple pathways (5,8,9). These studies have identified aqueous Mn(II) as a reaction end product but have not investigated the fate of Mn(III) in the dissolution process, even though Mn(III) is a necessary intermediate in the reduction of Mn(IV) to Mn(II) (10) and an important component of environmental systems (11).The photochemistry of Mn also enables solar energy harvesting (12) and water oxidation catalysis in synthetic and biological systems (3,13,14). Mn-based cluster compounds (15, 16) and disordered birnessite nanoparticles (2) can exhibit analogous reactivity to the water-oxidizing center of photosystem II.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that these mutational enrichment periods correspond to the adaptation of key oxygen‐sensitive components of Rubisco prior to the GOE (Anbar et al., 2007; Planavsky, Reinhard, et al., 2014). This would further indicate that calibrating the Rubisco tree to the appearance of cyanobacterial fossils or the GOE itself must be undertaken with care, given the possibility that stem group oxygenic photosynthetic organisms could have existed long before the appearance of recognizable Cyanobacteria in the fossil record (Blankenship & Hartman, 1998; Cardona, 2016; Fischer, Hemp, & Johnson, 2016; Johnson et al., 2013). Phenotypic characterization of expressed and purified ancestral forms of Rubisco may provide a biochemical and physiological basis for correlating the specific site mutations between the Anc.…”
Section: Discussionmentioning
confidence: 99%
“…The final step would have been the transition from oxidizing environmental Mn II (possibly with the help of uv) one at a time as a substrate, to oxidizing a portable Mn III reserve in the cluster of the water splitting apparatus at the periplasmic side of PSII [69]. Recently, geochemical evidence was reported that is in agreement with both that scenario [70] and the model of Dismukes and colleagues [65,71], which also suggested a role for environmental Mn II while also pointing out a role for high CO 2 in the origin of water splitting. The Mn-oxidizing abilities of RCII from Rhodobacter [72] are also compatible with the models deriving water splitting complex from environmental Mn II .…”
Section: Plastid Origin and The Origin Of Oxygenic Photosynthesismentioning
confidence: 60%